2021
DOI: 10.1002/bbb.2225
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of the U.S. corn ethanol industry for 20052019: implications for greenhouse gas emission reductions

Abstract: Since 2000, corn ethanol production in the USA has increased significantly – from 1.6 to 15 billion gallons (6.1 to 57 billion liters) – due to supportive biofuel policies. In this study, we conduct a retrospective analysis of the changes in US corn ethanol greenhouse gas emission intensity, sometimes known as carbon intensity (CI), over the 15 years from 2005 to 2019. Our analysis shows a significant decrease in CI: from 58 to 45 gCO2e/MJ of corn ethanol (a 23% reduction). This is due to several factors. Corn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 20 publications
1
25
0
2
Order By: Relevance
“…Thermal energy requirements in ethanol facilities have trended downward as reflected in a recent GREET retrospective published by Lee et al The low-end thermal energy requirement tested here reflects the 2017 update to GREET model at 26,487 Btu/gal, approximately 9% lower than BASE. The high-end case tests a thermal requirement of 32,043 Btu/gal which is the assumption in the 2016 iteration of the NREL ethanol cost model that served as the basis of the TEA .…”
Section: Resultsmentioning
confidence: 78%
“…Thermal energy requirements in ethanol facilities have trended downward as reflected in a recent GREET retrospective published by Lee et al The low-end thermal energy requirement tested here reflects the 2017 update to GREET model at 26,487 Btu/gal, approximately 9% lower than BASE. The high-end case tests a thermal requirement of 32,043 Btu/gal which is the assumption in the 2016 iteration of the NREL ethanol cost model that served as the basis of the TEA .…”
Section: Resultsmentioning
confidence: 78%
“…Currently, standards are being developed by the GHG Protocol that give guidance on this methodological issue. The exclusion of LUC considerations may lead to contradicting insights (e.g., Lee et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Higher energy input is then needed to produce corn and convert it into bioethanol. However, Lee et al (2021) have recently reported that corn-based bioethanol biorefineries have introduced newer techniques to increase bioethanol yield, reduce energy use, and add extra by-products. They suggest that stemming from innovation in bioethanol technology may certainly help reduce the GHG emissions of corn bioethanol.…”
Section: The Production and Utilization Of Bioethanol As A Biofuelmentioning
confidence: 99%